Avaliação do perfil psicossocial de pacientes anoftálmicos com indicação de prótese ocular - Bannwart, Lisiane Cristina [UNESP] (2009)
The loss or distortion one the eye due traumatic, congenital or pathological causes major psychological impact that effects are extended to the professional and social life of the individual. Despite surgical resources have progressed in recent years; there are cases where the repair in living tissue is non-indicated. For these cases, there is the alternative of ocular prosthesis. The purpose this study is evaluating the psychosocial profile of individuals who suffered eye losses, from the time of surgery to use the prosthetic eye and, analyze the effectiveness of rehabilitation with prostheses. For the purposes of evaluation, a form was used - Form of the psychosocial profile of patients with anophthalmic indication of ocular prosthesis, in order to analyze the expectations of patients prior to installation of prostheses and their satisfaction after use. This questionnaire was applied in 40 patients 10 to 80 years from Centro de Oncologia Bucal (COB) of Araçatuba Faculty of Dentistry, UNESP. It was contained open and closed questions that applied the purposes of this study. It was found predominance of man (65%), average age of 47 years, and 80% reported fear and concern as the main feelings. The reason trauma was reported by 60% of patients, 45% reported that adaptation to the first prosthesis was excellent or good, 52.5% reported facing prejudice and the most patients indicated the the work of medical ophthalmologist prostheses and support staff as good, great or regular. This survey helped to find a profile of psychosocial patients at the Center for Oral Oncology